Qualidade de vida, conhecimento e atitude de indivíduos com diabetes Mellitus após participação em programa educativo - Brito, Gabriela Menezes Gonçalves de (2016)
It is recognized that there are still knowledge gaps of individuals with type 2 diabetes mellitus about the disease and treatment and coping with situations arising in everyday life to control the disease. These weaknesses raise the importance of offering educational programs to promote a better quality of life, acquiring knowledge and readiness for coping with the disease for individuals with type 2 diabetes mellitus Objective: To evaluate the quality of life, knowledge and attitude of individuals with diabetes mellitus after taking part in an educational program Method: quasi-experimental, prospective, comparative, pre- and post held at the Endocrinology Clinic of the University Hospital of the Federal University of Sergipe, in 2015. The sample consisted of 110 individuals who were subdivided into Test Group (TG) and control group (CG). Discontinuity established criteria consisted of the presence of the participants in at least two proposed interventions in the educational program. The GT (n = 36) participated in five educational interventions and the control group (n = 74) of outpatient care routine every three months. To collect questionnaire data were used to obtain sociodemographic and clinical variables; the WHOQOL-bref and the B-PAID for evaluation of quality of life; the DKN-A, for knowledge and ATT-19, for the attitude. Results: the GT and GC, the psychological domain of the WHOQOL-BREF showed the highest average (14.98 and 14.22) and the Environment, the lowest (12.94 and 12.98), respectively. There was a statistically significant difference between the front groups to the domain Social Affairs, and the GT showed a better evaluation (p = 0.05). With respect to Measure B-PAID, it was observed that there was a decrease of suffering in living with MD in both groups, the second phase of the research, which was statistically significant, with the largest difference found in GT, pointing out that this group had lower suffering. There was acquiring knowledge about the disease and treatment in GT and the difference between the means was statistically significant (p = 0.01). On the attitude, there was a slight increase in GT and reduced GC. Conclusion: The educational program for individuals with type 2 diabetes mellitus contributed to the increase in QoL, including the reduction of suffering; increased knowledge about the disease and treatment and to better face the disease.